Circular RNAs in cancer: an emerging key player. Issue 1 (December 2017) - Dong, Yeping; He, Dan; Peng, Zhenzi; Peng, Wei; Shi, Wenwen; Wang, Jun; Li, Bin; Zhang, Chunfang; Duan, Chaojun
Abstract Circular RNAs (circRNAs) are a class of endogendous RNAs that form a covalently closed continuous loop and exist extensively in mammalian cells. Majority of circRNAs are conserved across species and often show tissue/developmental stage-specific expression. CircRNAs were first thought to be the result of splicing error; however, subsequent research shows that circRNAs can function as microRNA (miRNA) sponges and regulate splicing and transcription. Emerging evidence shows that circRNAs possess closely associated with human diseases, especially cancers, and may serve as better biomarkers. After miRNA and long noncoding RNA (lncRNA), circRNAs are becoming a new hotspot in the field of RNA of cancer. Here, we review biogenesis and metabolism of circRNAs, their functions, and potential roles in cancer.